A Virtual Electric Machine Laboratory for Effect of Saturation of the Asynchronous Machine Application - Tanyildizi, E.; Orhan, A. (John Wiley & Sons Inc, 2009)
Engineering education requires theoretical backgrounds to be supported by practical experience. Traditional laboratory practices are the supplementary parts of an education program which provide students practical skills and prepare them for professional life. However, since the real experiments are not always possible to carry out due to the limitations in equipments, suitable places, and sometimes limited time, alternative teaching means are needed. in this study, virtual application of asynchronous machine in a constant reference frame is given by a practical and functional interface, which can be a supportive tool for electrical engineering education. Asynchronous motor is generally modeled assuming constant parameters and linear inductance in transient analysis. However, many motors are designed for running in saturation region. In this application, magnetic saturation effect is also considered. All controls and variables of virtual application can be observed and saved in real time. An educational approach is adopted here to develop a virtual lab which can be used as a tool for education and demonstrative purposes. (C) 2009 Wiley Periodicals. Inc. Comput Appl Eng Educ 17: 422-428, 2009 Published online in Wiley InterScience (www.interscience.wiley.com); DOI 10.1002/cae.20229
Keywords: virtual laboratory; asynchronous motor; magnetic saturation; distant education